Exhaust gas treatment catalyst, and production method thereof

JP2023141041A5Pending Publication Date: 2025-03-21JGC CATALYSTS & CHEMICALS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022047163
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing exhaust gas treatment catalysts are less efficient in removing nitrogen oxides (NOx) in the presence of nitrogen dioxide (NO2) and carbon dioxide (CO2), particularly at temperatures below 200°C, and there is a need for catalysts that maintain high activity in the presence of these gases.

Method used

A composite oxide containing vanadium and molybdenum adhered to the surface of a titanium oxide carrier, with a specific Ca/S atomic concentration ratio, stabilized by a Ca compound and acrylate latex, is used to form a mixed valence compound of vanadium and molybdenum, enhancing selective reduction activity.

Benefits of technology

The catalyst maintains high nitrogen oxide removal efficiency even in the presence of nitrogen dioxide and carbon dioxide, exhibiting selective reduction activity across a wide temperature range, especially between 170°C and 270°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000013_0000
    Figure 00000013_0000
  • Figure 00000013_0001
    Figure 00000013_0001
  • Figure 00000013_0002
    Figure 00000013_0002
Patent Text Reader

Abstract

To provide an exhaust gas treatment catalyst having high removal efficiency of nitrogen oxide even in the presence of SOX.SOLUTION: In an exhaust gas treatment catalyst, complex oxide containing vanadium and molybdenum is fastened onto the surface of titanium oxide, and in XPS, the ratio of a surface atomic concentration of CA and S (Ca / S) is 0.6-2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention is SO X This invention relates to an exhaust gas treatment catalyst that exhibits high nitrogen oxide removal efficiency even in the presence of nitrogen oxides, and to a method for producing the same. [Background technology]

[0002] Conventionally, nitrogen oxides (NOx) in exhaust gas X As an exhaust gas treatment catalyst that selectively reduces and removes NO with a reducing agent such as ammonia, honeycomb-shaped catalyst molded products are used industrially, in which active components such as tungsten oxide and vanadium oxide are supported on a titanium oxide support containing alkali metals and alkaline earth metals (Patent Documents 1-3), and the valence of V and NO X Studies have also been conducted on the relationship with the conversion rate (Non-patent documents 1-5). In recent years, it has also been used as a catalyst to remove nitrogen oxides from exhaust gases of boilers, waste incinerators, etc., and from the perspective of suppressing the generation of dioxins, operation at temperatures below approximately 200°C is desired. X There is a growing demand for exhaust gas treatment catalysts that remain highly active even in the presence of certain substances. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2014-079683 [Patent Document 2] Japanese Patent Publication No. 2015-182067 [Patent Document 3] Japanese Patent Publication No. 2013-091045 [Non-patent literature]

[0004] [Non-Patent Document 1] Geert Silversmit et al., Determination of the V2p XPS binding energies for different vanadium oxidation states(V5+toV6+), J. Electron Spectroscopy and Related Phenomena, 2004, 135(2-3), 167-175. [Non-Patent Document 2] Geert Silversmit et al., An XPS study on the surface reduction of V2O5(001) induced by Ar+ion bombardment, Surface Science, 2006, 600(17), 3512-3517. [Non-Patent Document 3] Xuteng Zhao et al., A relationship between the V4+ / V5+ratio and the surface dispersion, surface acidity, and redox performance of V2O5-WO3 / TiO2 SCR catalysts, RSC Advances, 2018, 8, 31081-31093. [Non-Patent Document 4] Jiaoyan Zhou et al., Manipulating Behaviors from Heavy Tungsten Doping on interband Electronic Transition and Orbital Structure Variation of Vanadium Dioxide Films, ACS Appl. Mater. Interfaces, 2018, 10(36), 30548-30557, [Non-Patent Document 5] Jihene Arfaoui et al., A new V2O5 -MoO3 -TiO2 -SO42- nanostructured aerogel catalyst for diesel DeNO x technology, New Journal of Chemistry, Royal Society of Chemistry, 2020, 44 (37), pp.16119-16134

Summary of the Invention

Problems to be Solved by the Invention

[0005] The present invention aims to provide an exhaust gas treatment catalyst with high nitrogen oxide removal efficiency even in the presence of SO[[ID=ll]] X and a method for producing the same.

Means for Solving the Problems

[0006] The present inventors have intensively studied to solve the above problems and completed the present invention. The present invention is as follows [1] to [4]. [1] An exhaust gas treatment catalyst in which a composite oxide containing vanadium and molybdenum is fixed on the surface of a carrier containing a titanium oxide, and in XPS, the ratio (Ca / S) of the surface atomic concentrations of Ca and S is 0.6 to 2. [2] The exhaust gas treatment catalyst according to [1] above, wherein the composite oxide is composed of a mixed valence compound of vanadium and molybdenum containing trivalent, tetravalent and pentavalent vanadium and hexavalent molybdenum. [3] The exhaust gas treatment catalyst according to any one of [1] or [2] above, wherein the catalyst contains a Ca compound and / or a compound or mixture containing Ca and an acrylate latex. [4] 1) A step of kneading water, sulfuric acid, a vanadium raw material, a molybdenum raw material and a complexing agent to prepare a mother liquor, 2) A step of kneading a titanium oxide powder and the mother liquor to prepare a kneaded product, kneading a precipitating agent into the kneaded product, and obtaining a kneaded product for molding containing Ca in which a coprecipitate of vanadium and molybdenum is fixed on the surface of the titanium oxide powder. 3) A step of molding the kneaded material for molding to obtain a molded body. 4) A step of firing the molded body to obtain an exhaust gas treatment catalyst in which a composite oxide of vanadium and molybdenum is fixed to the surface of the titanium oxide powder. A method for producing an exhaust gas treatment catalyst including the above steps.

Effects of the Invention

[0007] The exhaust gas treatment catalyst of the present invention is an exhaust gas treatment catalyst that maintains a high nitrogen oxide removal efficiency even in the presence of SO X . Also, since the selective reduction activity of NO X is high, NO X can be efficiently removed not only in the high temperature range but also in the low temperature range of about 200 °C or lower.

Brief Description of the Drawings

[0008] [Figure 1] XPS spectrum (Ca, S) of the exhaust gas treatment catalyst obtained in Example 1. [Figure 2] SEM-EDS mapping image of the exhaust gas treatment catalyst obtained in Example 1. [Figure 3] XPS spectrum (Ca, S) of the exhaust gas treatment catalyst obtained in Comparative Example 1.

Modes for Carrying Out the Invention

[0009] Hereinafter, embodiments of the present invention will be described in more detail.

[0010] <The exhaust gas treatment catalyst of the present invention> The exhaust gas treatment catalyst of the present invention is an exhaust gas treatment catalyst in which a composite oxide containing vanadium and molybdenum is fixed to the surface of a carrier containing titanium oxide, and in XPS, the ratio (Ca / S) of the surface atomic concentrations of Ca and S is 0.6 to 2.

[0011] The composite oxide of vanadium and molybdenum preferably consists of a mixed valence compound containing trivalent, tetravalent and pentavalent vanadium and hexavalent molybdenum. By analyzing the surface of the exhaust gas treatment catalyst of the present invention by X-ray photoelectron spectroscopy (XPS) described in the following examples, it can be confirmed that it is a composite oxide containing vanadium and molybdenum of these valences.

[0012] The composite oxide of vanadium and molybdenum mentioned here is fixed to the surface of the carrier containing titanium oxide. This is different from the composite oxide in which vanadium, molybdenum and titanium are mixed in the same crystal structure. At most, the composite oxide of vanadium and molybdenum is fixed to the surface of the carrier containing titanium oxide through oxygen. Thereby, the phase of the composite oxide and the phase of the titanium oxide are clearly distinguished.

[0013] By adding a Ca compound, the state of the composite oxide of vanadium and molybdenum fixed to the surface of the carrier containing titanium oxide through oxygen of the composite oxide is stabilized.

[0014] The relationship between these metal oxides and Ca and S was confirmed by SEM-EDS mapping.

[0015] The composite oxide preferably contains vanadium in terms of V2O5 conversion of 3.0 to 10.0% by mass, more preferably 3.0 to 8.0% by mass, and molybdenum in terms of MoO3 conversion of 3.0 to 20.0% by mass, more preferably 3.0 to 8.0% by mass based on the catalyst standard.

[0016] The exhaust gas treatment catalyst of the present invention is one in which vanadium and molybdenum are fixed on titanium in the oxide state of suitable active species. In addition, the exhaust gas treatment catalyst of the present invention has a ratio (Ca / S) of the surface atomic concentrations of Ca and S of 0.6 to 2 in the measurement by XPS shown in the examples described later.

[0017] Conventionally, exhaust gas treatment catalysts with a large specific surface area have NO XIt is known to have good selective reduction activity. In contrast, the exhaust gas treatment catalyst of the present invention has good NO reduction activity even with a small specific surface area. X It exhibits selective reduction activity. Specifically, at 100m 2 Even if it is less than / g, 50m 2 / g or more 95m 2 Even in the range of less than / g, good NO X It exhibits selective reducing activity.

[0018] The exhaust gas treatment catalyst of the present invention may contain components other than the vanadium and molybdenum composite oxide. For example, components other than vanadium and molybdenum may include metal components such as tungsten, chromium, manganese, iron, nickel, copper, silver, gold, palladium, yttrium, cerium, neodymium, indium, iridium, and antimony. These act as co-catalysts and affect the catalytic performance, and their content (in terms of metal oxides) is preferably 3% by mass or less.

[0019] The exhaust gas treatment catalyst of the present invention contains sulfur. The sulfur content (SO4 equivalent) is preferably in the range of 0.1% to 5% by mass, more preferably in the range of 0.5% to 4% by mass, and particularly preferably in the range of 0.5% to 3% by mass. The sulfur contained in the exhaust gas treatment catalyst of the present invention affects the band structure of vanadium, and NO X It has a positive effect on selective reduction activity.

[0020] The exhaust gas treatment catalyst of the present invention contains a Ca compound and / or a Ca-containing compound or a mixture thereof. Preferably, the content of the Ca compound and / or Ca-containing compound or mixture is 1% by mass or more and 5% by mass or less. Examples of Ca compounds include calcium carbonate and calcium nitrate. Examples of compounds containing Ca include Ca-containing reinforcing materials and plasticizers (such as glass fibers and silane coupling agents).

[0021] In addition to these components, additives may be added during the molding process. Examples of additives include reinforcing agents and plasticizers. The catalyst may also contain inorganic components such as silane coupling agents, glass fibers, silica, and alumina as additives. These components enhance the moldability of the exhaust gas treatment catalyst and maintain its strength. Furthermore, it is preferable to add latex as an additive, and more preferably to add acrylate-based latex. By adding this additive, a silane coupling agent, and glass fibers, vanadium and molybdenum can be fixed to titanium in a preferred oxide state in a highly dispersed state. This contributes to improving catalytic performance. When reinforcing materials and plasticizers are used as additives, the total content of the reinforcing materials and plasticizers relative to the total amount of the exhaust gas treatment catalyst of the present invention is preferably 5 to 30% by mass. More preferably, it is 5 to 15% by mass. When latex, preferably acrylate latex (for example, with a concentration of 45%), is used as an additive, the content of latex (preferably acrylate latex) relative to the total amount of raw materials when manufacturing the exhaust gas treatment catalyst of the present invention is preferably 0.02 to 5.0% by mass. More preferably, it is 0.05 to 1.0% by mass.

[0022] The exhaust gas treatment catalyst of the present invention preferably comprises a Ca compound and / or a Ca-containing compound or a mixture thereof and an acrylate latex.

[0023] The shape of the exhaust gas treatment catalyst of the present invention may be a conventionally known shape such as a pellet or a honeycomb, and a honeycomb is preferred. To explain using a honeycomb with a square cross-sectional shape perpendicular to the longitudinal direction (through-direction) of the through-hole as an example, it is preferable that the outer diameter of the honeycomb (the length of one side of its cross-section) be in the range of 30 mm to 300 mm, and more preferably in the range of 50 mm to 200 mm. The length of the honeycomb (length in the longitudinal direction of the through-hole) is preferably in the range of 100 mm to 3000 mm, and more preferably in the range of 300 mm to 1500 mm. The through-holes in the honeycomb (hereinafter sometimes referred to as cell pitch) are preferably in the range of 1 mm to 15 mm in terms of the equivalent diameter of an equal-area circle in the cross-section, and more preferably in the range of 2 mm to 10 mm. The thickness of the honeycomb partitions is preferably in the range of 0.1 mm to 2 mm, and more preferably in the range of 0.1 mm to 1.5 mm. The opening ratio of the honeycomb is preferably in the range of 60% to 85%, and more preferably in the range of 70% to 85%. The opening ratio is defined as the ratio of the area where the catalyst is not present (the area occupied by the catalyst) to the cross-sectional area of ​​the honeycomb catalyst in the direction of the reaction exhaust gas flow velocity. When the honeycomb shape is within this range, the strength of the honeycomb structure is maintained while the NO per unit volume is reduced. X Selective reduction activity tends to increase.

[0024] The exhaust gas treatment catalyst of the present invention is NO X Exhaust gas containing NO, especially from boilers or waste incinerators, X Ya SO X NO is produced by catalytic reduction of exhaust gas containing heavy metals and dust by adding a reducing agent such as ammonia. X It is suitably used in removal methods. Furthermore, the operating conditions for the exhaust gas treatment catalyst are the same as those for normal exhaust gas treatment, specifically, it can be used at a reaction temperature of 150°C to 400°C. In particular, the exhaust gas treatment catalyst of the present invention shows high activity in the temperature range of 170°C to 270°C, and especially in the temperature range of 170°C to 200°C, it produces good NO X It exhibits selective reducing activity.

[0025] <Method for manufacturing the exhaust gas treatment catalyst of the present invention> The method for producing the exhaust gas treatment catalyst of the present invention is described below. The exhaust gas treatment catalyst of the present invention can be prepared, for example, by a manufacturing method comprising the following steps. 1) A step of preparing a mother liquor by kneading water, sulfuric acid, vanadium raw material, molybdenum raw material, and complexing agent. 2) A step of preparing a compound by kneading titanium oxide powder and the mother liquor, and then kneading a precipitating agent into the compound to obtain a moldable compound containing Ca, in which a coprecipitate of vanadium and molybdenum is fixed to the surface of the titanium oxide powder. 3) A step of molding the molding paste to obtain a molded body. 4) A step of firing the molded body to obtain an exhaust gas treatment catalyst in which a composite oxide of vanadium and molybdenum is fixed to the surface of the titanium oxide powder.

[0026] The following details each step. <Steps for preparing the mother liquor> In the process of preparing the mother liquor, vanadium raw materials, molybdenum raw materials, a complexing agent, and sulfuric acid are dissolved in water to prepare the mother liquor. Here, vanadium and molybdenum serve as raw materials for forming the complex oxide. The complexing agent coordinates with vanadium or molybdenum ions to form a complex. By dissolving these raw materials in water, the mother liquor can be prepared.

[0027] For the vanadium and molybdenum raw materials, it is preferable to use soluble salts. For example, vanadate salts, vanadium sulfate, or vanadium chloride are preferred as vanadium raw materials, and ammonium metavanadate is particularly preferred. Vanadium oxide may also be dissolved in acid. As the molybdenum raw material, it is preferable to use molybdate salts, molybdenum sulfate, or molybdenum chloride, and it is particularly preferable to use ammonium molybdate. Alternatively, molybdenum oxide may be dissolved in acid. Furthermore, these may be used individually or in combination of two or more types. Furthermore, the amounts of vanadium and molybdenum added as raw materials are adjusted as appropriate to match the final composition of the exhaust gas treatment catalyst.

[0028] The complexing agent is preferably a compound having an amine and a hydroxyl group, more preferably an alkanolamine, and particularly preferably ethanolamine. These complexing agents coordinate with vanadium ions or molybdenum ions in the mother liquor to form a complex and stabilize it. Therefore, it is preferable to add the complexing agent after dissolving the vanadium and molybdenum raw materials in water.

[0029] In this case, the amount of complexing agent added is preferably in the range of 0.1 moles to 6 moles, and more preferably in the range of 0.5 moles to 3 moles, per mole of vanadium and molybdenum. By adding the amount of complexing agent necessary to form the complex in this way, the vanadium and molybdenum ions are stabilized.

[0030] The amount of sulfuric acid added is preferably in the range of 0.001 moles to 0.1 moles per mole of titanium, and more preferably in the range of 0.01 moles to 0.05 moles.

[0031] In the process of preparing this mother liquor, other soluble components may be added. For example, a raw material containing the aforementioned co-catalyst component may be dissolved.

[0032] <Process for obtaining a molded paste> In this step, the mother liquor prepared in the aforementioned step for preparing the mother liquor is kneaded with a powder containing titanium oxide to prepare a carrier containing titanium oxide. It is preferable that the powder containing titanium oxide is surface-modified beforehand with an acid. The acid used here can be either an inorganic acid or an organic acid, such as citric acid, acetic acid, nitric acid, phosphoric acid, or sulfuric acid.

[0033] The titanium oxide powder may consist of titanium oxide alone, or it may also contain other elements such as Si or Mo in addition to titanium oxide.

[0034] The kneaded product contains Ca compounds and / or Ca-containing compounds or kneaded products thereof. Preferably, the content of Ca compounds and / or Ca-containing compounds or kneaded products in the kneaded product is 1% by mass or more and 5% by mass or less. Examples of Ca compounds include calcium carbonate and calcium carbonate. Examples of compounds containing Ca include Ca-containing reinforcing materials and plasticizers (such as glass fibers and silane coupling agents).

[0035] It is preferable to include latex in the compound. The latex is preferably an acrylate-based latex. This is because vanadium and molybdenum can be fixed to the titanium in a suitable oxide state in a highly dispersed manner, thereby improving catalytic performance. The latex content in the kneaded mixture is preferably 0.02 to 5.0% by mass. More preferably 0.05 to 1.0% by mass.

[0036] The kneaded material may further contain additives such as reinforcing materials and plasticizers that may also be included in the exhaust gas treatment catalyst of the present invention. Specifically, it is preferable to include inorganic components such as glass fibers, silica, and alumina. Including inorganic components tends to improve the moldability and strength of the exhaust gas treatment catalyst. When reinforcing agents and plasticizers are used as additives, the total content of reinforcing agents and plasticizers in the compound is preferably 5 to 30% by mass. More preferably 5 to 15% by mass.

[0037] Conventional methods of mixing can be used. For example, a kneader, a high-speed mixer, or a ball mill can be used. These methods are appropriately selected depending on the amount of mother liquor and the amount of powder containing titanium oxide. If the mixture becomes clay-like and puts a load on the equipment, it is preferable to use a kneader or a high-speed mixer.

[0038] Subsequently, the carrier containing titanium oxide and the precipitant are kneaded together to prepare a moldable compound in which a coprecipitate of vanadium and molybdenum is fixed to the surface of the carrier containing titanium oxide. Here, the mother liquor components contained in the compound are neutralized, and a coprecipitate of vanadium and molybdenum is formed. This coprecipitate is fixed to the surface of the carrier containing titanium oxide to obtain a moldable compound.

[0039] Conventional precipitating agents can be used. For example, precipitating agents such as sodium carbonate, soda ash, and aqueous ammonia can be used. The amount of precipitating agent added is adjusted as appropriate so that the pH of the mother liquor contained in the kneaded mixture is in the range of 6 to 9. If the carrier containing titanium oxide is clay-like and it is difficult to measure the pH, the amount of precipitating agent needed to neutralize the mother liquor should be determined experimentally beforehand, and the amount added should be adjusted accordingly. If the carrier containing titanium oxide is not clay-like, the moisture content should be adjusted, a binder should be added, etc., to prepare a kneaded mixture suitable for molding.

[0040] <Process for obtaining a molded body> In the process of obtaining a molded body, the molded compound is molded to prepare the molded body. It can be molded into conventionally known shapes such as pellets or honeycomb. For applications as an exhaust gas treatment catalyst, it is preferable to mold it into a honeycomb shape. Regarding the molding method, conventionally known methods can be used; for example, the material can be molded into pellets or honeycomb structures using an extrusion molding machine. The molded body should be dried using conventionally known methods to prevent cracking or other damage. The aforementioned exhaust gas treatment catalyst of the present invention may contain additives such as reinforcing materials and plasticizers, which may be included in the molded body, by molding them together with the kneaded material for the molded body.

[0041] <Process for obtaining an exhaust gas treatment catalyst> In the process of obtaining the exhaust gas treatment catalyst, the molded body is calcined to prepare an exhaust gas treatment catalyst in which a composite oxide of vanadium and molybdenum is fixed to the surface of a support containing titanium oxide. Conventional known calcination methods can be used. For example, calcination in the atmosphere using a heating furnace such as an electric furnace or a gas furnace can be used. The calcination temperature is preferably between 300°C and 500°C. The calcination time depends on the calcination temperature, but is generally within the range of 1 hour to 48 hours. [Examples]

[0042] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited in any way to the examples provided.

[0043] [Measurement method] The measurement methods adopted in this application are described below.

[0044] [1] Composition The exhaust gas treatment catalysts obtained in the examples and comparative examples were powdered to prepare evaluation samples. A solution was prepared by dissolving this in acid, and the composition of various components was calculated using inductively coupled plasma emission spectroscopy (instrument name: ICPS-8100).

[0045] [2] Calculation of vanadium valency and surface atomic concentrations of calcium and sulfur Evaluation samples were prepared by fragmenting the reaction surfaces (outer surface for pellets, outer surface of the partitions for honeycomb) of the exhaust gas treatment catalysts obtained in the examples and comparative examples, so that these surfaces could be measured. These samples were placed on a sample stage and X-ray photoelectron spectroscopy (XPS) was performed under the following conditions. The spectra obtained from these measurements were analyzed to determine the valence of vanadium and to calculate the surface atom concentrations of calcium and sulfur (peak ranges are shown below). V 5+ :517.20eV±0.2eV V 4+ :515.84eV±0.2eV V 3+ :515.29eV±0.2eV Ca 2p: 348eV±2eV S 2p: 170eV±2eV <Measurement conditions> XPS measurements were performed using a ThermoFisher ESCALAB220IXL, with Al as the X-ray source. The peak position was corrected to a reference value of 284.8 eV for the CC coupling of C1S. After setting the evaluation sample in the instrument and confirming that high vacuum had been achieved, measurements were taken under the conditions of an acceleration voltage of 10 kV, an emission current of 10 mA, and 30 scans. <Calculation conditions> After scan integration, the built-in analysis software AVANTAGE is used to separate peaks for V. 3+ , V 4+ , V 5+ Check for the presence or absence of a peak. Similarly, the surface atom concentrations for Ca and S were calculated from the peak areas detected within the respective peak ranges mentioned above.

[0046] [3] Strength After cutting out 75mm x 75mm cubes from the catalysts obtained in Examples 1-3 and Comparative Examples 1-2, they were compressed perpendicular to the direction of penetration of the honeycomb through-holes, and the pressure at which the catalyst was completely destroyed was measured. The results are shown in Table 1.

[0047] [4] Specific surface area The exhaust gas treatment catalysts obtained in the examples and comparative examples were pulverized to prepare evaluation samples. A 0.2g evaluation sample was placed in a measuring cell and degassed at 300°C for 60 minutes in a nitrogen gas stream. The sample was then maintained at liquid nitrogen temperature in a mixed gas stream of 30% nitrogen and 70% helium by volume, allowing nitrogen to be adsorbed to equilibrium. Next, the sample temperature was gradually increased to room temperature while the mixed gas flowed through it. The amount of nitrogen desorbed during this time was detected, and the specific surface area of ​​the sample was measured using a pre-prepared calibration curve.

[0048] [5] SEM-EDS measurement The surface of the denitrification catalyst obtained in the examples was measured by SEM-EDS (energy-dispersive X-ray spectroscopy) under the following conditions. <Measurement conditions> SEM measurements were performed using a JEOL JSM6010LA with wtr as the X-ray source. The denitrification catalyst obtained in the examples was processed into fragments, and the surface that constitutes the denitrification reaction surface (the outer surface for pellets, or the outer surface of the partitions for honeycomb structures) was measured. The acceleration voltage was adjusted to 20kV-15kV, and the SS was adjusted to 4nm. Then, the image was magnified up to 1.5 million times, the analysis position was probe-tracked, and EDS-line analysis was performed to trace the measurement position, followed by compositional transformation by the ZAF method. <Calculation method> From the obtained data, the surface analysis results for Ti, V, Mo, Ca, and S were extracted and overlaid in Photoshop to analyze their respective positional relationships.

[0049] [6] Denitrification performance (selective reduction catalyst (SCR) activity) The exhaust gas treatment catalysts obtained in the examples and comparative examples were cut into the following catalyst shapes to prepare evaluation samples. These were packed into a flow-through reactor, and the denitrification rate was evaluated. Specifically, NO before and after catalyst contact was measured under the following conditions. X The denitrification rate was calculated from the concentration using the following formula. Furthermore, the denitrification rate immediately after circulating gas composition 1 for 3 hours was defined as the "initial denitrification rate," and the denitrification rate immediately after circulating gas composition 2 for 100 hours was defined as the "denitrification rate after accelerated degradation test." In Table 1, the "initial denitrification rate" is abbreviated as "denitrification performance (150°C / K value)," and the "denitrification rate after accelerated degradation test" is abbreviated as "SOx-resistant." X It was labeled "performance." Note that nitrogen oxides (NO) in the gas before and after contact with the catalyst X The concentration was measured using a chemiluminescent nitrogen oxide analyzer (ECL-88AO, manufactured by Anatech Yanaco Co., Ltd.). Denitrification rate (%) = [NOx in gas before contact] X (ppm) - NO in gas after contact X (ppm)] / NOx in gas before contact X (ppm) × 100 <Test Conditions> • Catalyst shape: 4x4 mesh, length 286mm Reaction temperature: 150℃ • Reaction time: 100 hours ·SV:18528.39h -1 • Gas composition 1: NO X =200ppm, NH3=200ppm, O2=5%, H2O=10%, N2=balance • Gas composition 2: NO X =200ppm, NH3=200ppm, O2=5%, H2O=10%, SO2=80ppm, N2=balance

[0050] [Example 1] <Preparation of titanium dioxide-containing powder for exhaust gas treatment catalyst (a)> A titanium sulfate solution obtained from the titanium dioxide production process using the sulfuric acid method was thermally hydrolyzed to obtain a metatitanic acid slurry with a TiO2 concentration of 30% by mass. A predetermined amount of this metatitanic acid slurry was taken out and placed in a stirred tank with a reflux condenser. 15% by mass of aqueous ammonia was added to adjust the pH to 9.5, then a predetermined amount of silica sol S-20L (manufactured by JGC Catalysts & Chemicals Co., Ltd.) was added, and the mixture was heated and matured at 95°C for 1 hour with sufficient stirring. After cooling, the slurry was taken out, filtered, dehydrated, and washed. The washed cake was dried at 110°C for 20 hours, then calcined at 400°C for 5 hours, and pulverized to obtain (a) a titanium dioxide-containing powder with an SiO2 / TiO2 weight ratio of 10% / 90%.

[0051] <Preparation process for mother liquor 1> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78% by mass) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5% by mass) was added, followed by stirring for 5 minutes. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 1 containing vanadium and molybdenum.

[0052] <Steps to obtain molding compound 1> Titanium dioxide-containing powder a (TiO2 = 90% by mass, SiO2 = 10% by mass, specific surface area (SA) = 150 m² 2 18920g of (18920g, oxide concentration 95% by mass) and 8276g of aqueous ammonia (concentration: 15% by mass) were added and kneaded in a kneader for 10 minutes. Then, 1150g of calcium carbonate was added, and 3000g of glass fiber was added as a structural restricting agent and kneaded for 10 minutes. Then, 4216g of Nipol LX874 (manufactured by Nippon Zeon Co., Ltd.), a 45% concentration acrylate latex, diluted 25 times with water was added, and the aforementioned mother liquor 1 was slowly added and kneaded for 30 minutes. Then, 703g of carboxymethylcellulose (manufactured by Nichirin Chemical Co., Ltd.; ammonium CMC) was added as a neutralizing agent for residual amines and kneaded for 10 minutes. Kneading was continued for 30 minutes while heating to evaporate the water. 2272g of anhydrous citric acid (manufactured by Fuso Chemical Co., Ltd.) was added and kneaded in a kneader for 20 minutes, after which the water was adjusted to obtain moldable compound 1.

[0053] <Steps to obtain exhaust gas treatment catalyst 1> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the moldable mixture 1 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends of the honeycomb through-holes in the central axis direction (longitudinal direction) were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 1 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.

[0054] Figure 1 shows the XPS spectra (Ca) and (S) of the exhaust gas treatment catalyst obtained in Example 1.

[0055] Figure 2 shows scanning electron microscope (SEM) EDS images of the exhaust gas treatment catalyst obtained in Example 1. Figure 2(a) is a 3000x SEM image. Figure 2(b) shows the distribution of Ca, Figure 2(c) shows the distribution of Mo, and Figure 2(d) shows the distribution of S. In each figure, the darker the color, the higher the concentration of each component. Figure 2(e) shows the distribution of S and Ca superimposed, and Figure 2(f) shows the distribution of S and Mo superimposed. From this image, it appears there is a relationship between the distribution of Ca and S and the distribution of catalytic components.

[0056] [Example 2] <Preparation process for mother liquor 2> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78% by mass) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5% by mass) was added, followed by stirring for 5 minutes. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 2 containing vanadium and molybdenum.

[0057] <Steps to obtain molding compound 2> 20766g of titanium dioxide (Tronox: G5: TiO2 oxide concentration 82% by mass), 2272g of anhydrous citric acid (Fuso Chemical Co., Ltd.), and 2000g of water were kneaded in a kneader for 10 minutes. Then, the aforementioned mother liquor 2 was added and kneaded for 30 minutes. Subsequently, 703g of carboxymethylcellulose (Nichirin Chemical Co., Ltd.; ammonium CMC) was added as a neutralizing agent for residual amines and kneaded for 10 minutes. 8276g of aqueous ammonia (concentration: 15% by mass) was added to the resulting mixture as a precipitating agent and kneaded for 30 minutes while heating to evaporate the water. Then, 3000g of glass fiber was added as a structural restricting agent and kneaded for 10 minutes. After that, 4216g of Nipol LX874 (Nippon Zeon Co., Ltd.), a 45% concentration acrylate latex, diluted 25 times with water, was added and kneaded for 20 minutes, and then 1150g of calcium carbonate was added to obtain molding mixture 2.

[0058] <Steps to obtain exhaust gas treatment catalyst 2> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the molded mixture 2 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 2 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.

[0059] [Example 3] <Preparation of titanium dioxide-containing powder for exhaust gas treatment catalyst (b)> A titanium sulfate solution obtained from the titanium dioxide manufacturing process using sulfuric acid was thermally hydrolyzed to obtain a metitanic acid slurry with a TiO2 concentration of 30%. A predetermined amount of this metitanic acid slurry was taken out and placed in a stirred tank with a reflux condenser. 15% by weight of aqueous ammonia was added to adjust the pH to 9.5, then a predetermined amount of S-20L (manufactured by JGC Catalysts & Chemicals Co., Ltd.) was added, and the mixture was heated and matured at 95°C for 1 hour with sufficient stirring. After cooling, the slurry was taken out, filtered, dehydrated, and washed. The washed cake was dried at 110°C for 20 hours, then calcined at 600°C for 5 hours, and pulverized to obtain a titanium dioxide-containing powder (b) with an SiO2 / TiO2 mass ratio of 10% / 90%.

[0060] <Preparation process for mother liquor 3> 6000g of water, 1359g of monoethanolamine as a complexing agent, and 2544g of ammonium metavanadate (manufactured by Shinko Chemical Co., Ltd.: V2O5 oxide concentration 78% by mass) were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C, and 2233g of ammonium molybdate (manufactured by Taiyo Mining Co., Ltd.: MoO3 oxide concentration 81.5% by mass) was added, followed by stirring for 5 minutes. Subsequently, 3654g of sulfuric acid (concentration: 25% by mass) was added to obtain mother liquor 3 containing vanadium and molybdenum.

[0061] <Step to obtain molding compound 3> Titanium dioxide-containing powder b (TiO2=90 mass, SiO2=10 mass, SA=90 m 2 17925g of (15% by mass) acrylate (oxide concentration 95%) and 8276g of aqueous ammonia (concentration: 15%) were added and kneaded in a kneader for 10 minutes. Then, 1150g of calcium carbonate was added, and 3000g of glass fiber was added as a structural restricting agent and kneaded for 10 minutes. Then, 4216g of Nipol LX874 (manufactured by Nippon Zeon Co., Ltd.), a 45% concentration acrylate latex, diluted 25 times with water was added, and the aforementioned mother liquor 3 was gradually added and kneaded for 30 minutes. Then, 703g of carboxymethylcellulose (manufactured by Nichirin Chemical Co., Ltd.; ammonium CMC) was added as a neutralizing agent for residual amines and kneaded for 10 minutes. Kneading was continued for 30 minutes while heating to evaporate the water. 2272g of anhydrous citric acid (manufactured by Fuso Chemical Co., Ltd.) was added and kneaded in a kneader for 20 minutes, after which the water was adjusted to obtain moldable compound 3.

[0062] <Steps to obtain exhaust gas treatment catalyst 3> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the moldable mixture 3 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 3 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.

[0063] [Comparative Example 1] <Preparation of titanium dioxide-containing powder for exhaust gas treatment catalyst (c)> A titanium sulfate solution obtained from the titanium dioxide production process using the sulfuric acid method was thermally hydrolyzed to obtain a metitanic acid slurry with a TiO2 concentration of 30%. A predetermined amount of this metitanic acid slurry was taken out and placed in a stirred tank with a reflux condenser. 15% by weight of aqueous ammonia was added to adjust the pH to 9.5, then a predetermined amount of S-20L (manufactured by JGC Catalysts & Chemicals Co., Ltd.) and a predetermined amount of ammonium paratungstate were added. The mixture was then heated and matured at 95°C for 1 hour with sufficient stirring. After cooling, the slurry was removed, filtered, dehydrated, and washed. The washed cake was dried at 110°C for 20 hours, then calcined at 600°C for 5 hours, and pulverized to obtain a titanium dioxide-containing powder (c) with a WO3 / SiO2 / TiO2 weight ratio of 2% / 1% / 97%.

[0064] <Preparation process for mother liquor 4> 3000g of water, 330g of monoethanolamine as a complexing agent, and 691.3g of ammonium metavanadate were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C to prepare mother liquor 4.

[0065] <Step to obtain molding compound 4> 18790g of titanium dioxide-containing powder c (TiO2=97% by mass / WO3=2% by mass / SiO2=1% by mass), 811.1g of ammonium metavanadate, 809.82g of ammonium molybdate, and aqueous ammonia (concentration: 15% by mass) were kneaded in a kneader for 30 minutes. Then, the mother liquor 4 prepared in the above step was added and kneaded for 30 minutes. Furthermore, 1710g of glass fiber was added as a structural restricting agent and kneaded for 10 minutes. Finally, 300g of an organic binder, which serves as a molding aid, was added and kneaded for 20 minutes to obtain a moldable mixture 4.

[0066] Figure 3 shows the XPS spectra (Ca) and (S) of the exhaust gas treatment catalyst obtained in Comparative Example 1.

[0067] <Step to obtain exhaust gas treatment catalyst 4> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the molded mixture 4 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 4 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.

[0068] [Comparative Example 2] <Preparation process for mother liquor 5> 3000g of water, 330g of monoethanolamine as a complexing agent, and 691.3g of ammonium metavanadate were prepared. After kneading these together, the temperature was raised to 80-90°C and stirring was continued for 2 hours. This was then cooled to 40-60°C to prepare mother liquor 5.

[0069] <Steps to obtain molding compound 5> 182,900 g of titanium dioxide (manufactured by Ishihara Sangyo Co., Ltd.: MC90: TiO2 oxide concentration 95% by mass), 1411.99 g of ammonium metavanadate, 1889.6 g of ammonium molybdate, and aqueous ammonia (concentration: 15% by mass) were kneaded in a kneader for 30 minutes. Then, the mother liquor 5 prepared in the above step was added and kneaded for 30 minutes. Furthermore, 1710 g of glass fiber was added as a structural restricting agent and kneaded for 10 minutes. Finally, 300 g of an organic binder, which serves as a molding aid, was added and kneaded for 20 minutes to obtain the moldable mixture 5.

[0070] <Steps to obtain exhaust gas treatment catalyst 5> Using a screw-type vacuum extruder equipped with a honeycomb extrusion die, the molded mixture 5 obtained in the aforementioned process was formed into a honeycomb. After drying this honeycomb for a sufficient amount of time, it was dried for two days with hot air at 60°C. Then, both ends in the central axis direction (longitudinal direction) of the honeycomb through-holes were trimmed, and it was fired in an electric furnace at 450°C for 5 hours under an atmospheric atmosphere to obtain an exhaust gas treatment catalyst 5 with a cell pitch of 2.8 mm and a wall thickness of 0.5 mm. The aforementioned measurements were performed on this exhaust gas treatment catalyst. The results are shown in Table 1.

[0071] Table 1

Claims

1. A composite oxide containing vanadium and molybdenum is fixed to the surface of a support containing titanium oxide, An exhaust gas treatment catalyst having a surface atomic concentration ratio of Ca to S (Ca / S) of 0.6 to 2 in XPS.

2. The exhaust gas treatment catalyst according to claim 1, characterized in that the composite oxide is a mixed valence compound containing trivalent, tetravalent and pentavalent vanadium and hexavalent molybdenum.

3. A process for preparing a mother liquor by dissolving sulfuric acid, a vanadium raw material, a molybdenum raw material, and a complexing agent in water; kneading the mother liquor with titanium oxide powder to prepare a kneaded mixture; a molding step of molding the kneaded mixture to obtain a molded body; and a step of calcining the molded body to obtain an exhaust gas treatment catalyst. The method for producing an exhaust gas treatment catalyst, wherein the kneaded material in the molding step contains a precipitant and calcium.